Correlation Study Between Emotional Intelligence (EI) and Parenting Styles Among Muslim Gifted and Talented Students - Nur Yasmin Maisarah Ahmad Mahyuddin,; Amirah Zainun (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 291-294